Paschen curve approach to investigate electron density and deposition rate of Cu in magnetron sputtering system. Issue 11 (1st December 2016) - Gopikishan, S.; Banerjee, I.; Bogle, K. A.; Das, A. K.; Pathak, A. P.; Mahapatra, S. K.
ABSTRACT: In this work, Paschen curve for argon gas was obtained during copper deposition using a DC magnetron sputtering system. Five process parameters of Paschen curve were used to obtain the electron density and deposition rate of the deposited nanostructured thin films. Plasma parameter such as electron density was correlated with the deposition rate. It is observed that a minimum deposition rate was obtained for the plasma process parameter corresponding to the Paschen minimum. This investigation helps to understand and optimize the quality of nanostructured thin films depending on the process parameters.